Electronic structure and thermoelectric properties of PbS1-xTex (x=0, 0.25, 0.50, 0.75, 1.0) alloys: Ab initio study. (December 2018) - Khan, Saleem Ayaz; Azam, Sikander
Abstract: We present electronic structure and thermoelectric behavior for the PbS1-x Tex (x = 0, 0.25, 0.50, 0.75, 1.0) using all electron full potential linearized augmented plane wave (FP-LAPW) method. The correct value of the band gap is achieved with fully relativistic calculation by employing spin orbit coupling to the Hamiltonian implicitly. Our study shows the interactions between Pb-s, Te-p and S-p states that play a leading role in the valance band while the Pb-p and S-p and Te-p states play a dominant role in conduction band. The thermoelectric properties discuss the variation of the electrical and thermal conductivity, Seebeck coefficient, power factor and figure of merit with temperature variation using the Boltzmann transport theory. The high-temperature figure of merit of Te doped PbS alloy have been found to be significantly greater than PbS. This improvement is associated to the ability to attain higher doping and, hence, larger electrical properties at high temperatures. Hence, it reveals that both PbS0.25 Te0.75 and PbTe can be used as promising materials for high potential thermoelectric device applications. Highlights: Complex studies of band structure for PbS1-x Tex (x = 0, 0.25, 0.50, 0.75, 1.0) have been done. With increasing the strain the band gap value is enhanced. At enhanced strain percentage, the states are moving towards the higher energy levels. Good agreement between DFT simulations and experiment is achieved. PbS1-x Tex is promising thermoelectric material in the high temperature range.